Analisis Efektivitas Penyaluran Zakat pada Badan Amil Zakat Nasional - Efri Syamsul Bahri; Sabik Khumaini (Prodi Perbankan Syariah FAI UMT, 2020)
The National Zakat Board (BAZNAS) The Republic of Indonesia is a non-structural government institution that manages zakat nationally in Indone. The problem in this research is how the development of the collection and distribution of Zakat, Alms, and Other Religious Social Funds (ZIS and DSKL) and how effective is the distribution of BAZNAS zakat? The objectives of this study include: to measure the effectiveness of the distribution of BAZNAS ZIS and DSKL. This research uses qualitative and quantitative methods. The qualitative method uses a descriptive approach. While the quantitative method uses the Zakat Core Principle (ZCP) measurement model. The object used in this study is the BAZNAS financial statements for the period 2001 to 2018. The results of this study indicate that the total collection of ZIS and DSKL is 18 years, Rp932.648.351.752,19. While the amount of ZIS and DSKL distribution for 18 years, is Rp836.512.139.145,00. Based on the ZCP the effectiveness of distribution for 18 years of operation is 90% (ninety percent). This shows that the effectiveness of the distribution of ZIS and DSKL BAZNAS for 18 years is in the Highly Effective category where the Allocation to Collection Ratio (ACR) reaches ≥ 90 percent.